Mining as the "Locomotive of the Colombian Economy" : It´s Real Cost (2017)
ABSTRACT: For the past 15 years, the Colombian government has enacted laws promoting large-scale mining across the country with the banner of the sector becoming the engine for growth and development of the country. By declaring it an “activity for public utility and social interest”, expropriations, forced displacements, and licenses to operate in protected areas have been pervasive. Out of the 114 million hectares of the Colombian territory, the area dedicated to mining grew from 1.1 million hectares in 2001 to 5.34 million in 2010. Furthermore, a recent decree declared an area that encompasses 22.2 million hectares as “strategic mining sites” (Resolution 045 of 2012), which covers vast areas of the Amazon jungle and 18% of the national territory. The revenues have not translated in building up Colombia´s inadequate infrastructure or improving the productivity and competitiveness of sustainable sectors of the economy. Furthermore, the expansion of both industrial and artisanal mining has worsened social conflicts and increased poverty in mining regions. The rise in gold production has been paralleled by increased imports of elemental mercury, sodium cyanide, and proliferation of illegal mining operations. With these antecedents, this document provides arguments to consider the mining “boom” in Colombia as “adverse to” rather than as a “potentiator” of the prosperity and peace of the country. A few studies that are representative of the environmental consequences of industrial and artisanal gold mining, such as destruction of tropical forests, are used to illustrate some issues of concern.